The Effect of Spray-Dried Bovine Plasma and Shrimp Hydrolysate on Components of the Immune System and Zootechnical Parameters in Broiler Chickens - Parra , G.; Mier, N.; Aguirre, A.; Riboty, R. (International Journal of Poultry Science, 2019)
Background and Objective: The aim of this study was to evaluate the immunomodulatory effect of spray-dried bovine plasma (SDBP) and shrimp hydrolysate (SH) in components of the immune system and its influence on zootechnical parameters in broiler chickens raised at 2500 m.a.s.l. Materials and Methods: One thousand five hundred one-day-old mixed Cobb broilers were divided into four groups with five replicates each in a randomized block design. The animals were raised in a challenging manner, that is with reused and untreated litter and without being vaccinated against Avian pneumovirus (APV). A three-phase (1-14, 15-28 and 29-42 days) restricted mash feeding program was used. Birds of the five experimental units were fed for 42 days, with one of the following treatments: a corn and soybean basal diet (Control), SDBP or SH reformulated diets under two dosing strategies (S1 and S2). Inclusion levels were 5, 2.5,1.5% in S1 and 2.5%, 1.5%, 0.5% in S2 on the three-phase feeding program. Results: In the first week, the SDBP S2 avoided a drastic drop in maternal antibodies against APV and produced better white blood cell percentages. In week 6, similar results in white blood cell percentages were observed with SDBP S1, SDBP S2 and SH S1. The SDBP S2 generated a better performance than the control group throughout the fattening cycle and the SH S2 produced the same effect as the control group. The treatments produced no significant effect on the immune organ indices and the mortality rate. Conclusion: The inclusion of SDBP S2 in broiler chickens’ diet has a more evident immunomodulatory effect in white blood cells and maternal antibodies without vaccination and has a positive effect on the animals’ performance.